Plasma metabolomic profile in fibrosing pulmonary sarcoidosis - Mirsaeidi, Mehdi; Banoei, Mohammad Mehdi; Nienow, Caleb K; Abassi, Taimur; Hakim, Anoushirvan; Schraufnagel, Dean; Winston, Brent W; Sweiss, Nadera; Baughman, Robert; Garcia, Joe G. N.; Machado, Roberto (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2016)
Background: There is no known marker to screen patients with sarcoidosis to determine the risk of progression to pulmonary fibrosis. We aimed to identify potential noninvasive biomarkers for early detection of pulmonary fibrosing sarcoidosis. Methods: A case-control study was performed on African Americans with confirmed sarcoidosis included 31 subjects with pulmonary fibrosis vs. 36 without pulmonary fibrosis. Plasma samples were analyzed by liquid chromatography-mass spectrum. Multivariate statistical analysis models were developed in a training set based on 50 age- and sex-matched samples to identify metabolites involved in the discrimination. Principal component analysis and orthogonal partial least squares-discriminant (OPLS) analysis coupled to the most influential variables were used to derive significant metabolic discriminations. Results: Of the datasets from 171 feature peaks, 14 features including p-coumaroylagmatine and palmitoylcarnitine showed significant differences between fibrosing and non-fibrosing pulmonary sarcoidosis (p = 0.001). OPLS analysis presented clear separation between two groups with an acceptable goodness of fit (R2 = 0.522) and predictive power (Q2=0.322). Discriminating metabolites involved collagen pathway metabolites especially those in the arginine-proline pathway. Conclusions: Metabolomics can provide a useful tool to detect pulmonary fibrosis in patients with sarcoidosis. Two discriminating metabolites, p-coumaroylagmatine and palmitoylcarnitine may be potential markers for fibrosing pulmonary sarcoidosis.